Transformasi Ekonomi Nelayan dan Pembudidaya Ikan melalui Inovasi Teknologi dan Digitalisasi - Pahlevi, Muhamad Reza; Pratama, Juanis; Nurfikriyanto, Yogi; Ihsan, Muhammad Fadlih (Jurnal Ekonomi Laut dan Air Tawar, 2025)
The economic transformation of fishermen and fish farmers has become a crucial issue in addressing the challenges of globalization and technological change. This article aims to analyze the role of technological innovation and digitalization in improving the economic welfare of fishermen and fish farmers. This study employs a descriptive qualitative method with a case study approach conducted in several coastal regions of Indonesia. The findings indicate that the adoption of digital technology within the fisheries sector enhances production efficiency, expands market access, and elevates the competitiveness of both fishermen and fish farmers. However, several barriers persist, including limited technology access, low digital literacy, and infrastructural constraints. This article also proposes solutions in the form of capacity building through digitalization training, strengthening the fisheries technology ecosystem, and developing policies that support technology adoption for fishermen and fish farmers. The results demonstrate that preserving local wisdom by empowering community organizations serves as a key factor for sustainable innovation in this sector. Consequently, digitalization and technological innovation can serve as primary drivers in the economic transformation of Indonesia's fisheries sector.